Influence of climate and mixture effect on radial increment of European beech (Fagus sylvatica) in pure and mixed stands with Scots pine (Pinus sylvestris) - Szeptun, Jakub (SLU/Southern Swedish Forest Research Centre, 2015)
The main aim of this study was to investigate the trends of radial increment of European Beech (Fagus sylvatica L.) in pure stands and mixed stands with Scots pine (Pinus sylvestris L.). The study plots were located in Kivik and Tyringe in Skåne which is the southernmost region of Sweden. Applied methods were based on analyze of tree ring widths in cores extracted from trees. The factor mostly influencing the radial increment turned out to be trees’ age (p<0,001). Stands were losing their growth potential with growing age, however the pattern differed between the stands. Precipitation had also statistically significant (p<0,001) but minor impact on increment of beech in June and July. Temperature and mixture effect were found to have no effect on radial increment (p>0,05). Further analysis showed that the investigated period (1961-2013) can be divided into three minor periods which are characterized by specific relations between beech and pine. On the basis of mentioned results multiple regression model was created, to predict radial increment with varying input values of age, precipitation, temperature and mixture. The number of plots in this study was found to be insufficient to give certain results on radial increment trends of beech but it is a part of European EuMixFor transect study on beech and pine which may bring significant input to knowledge on mixed forests in the future.